(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Plants have several chemical compounds acclaimed to be responsible for the pharmacological actions produced when herbal products are administered to biological systems. Objectives: This study was designed to investigate the anti-inflammatory effect of the alkaloid-rich fraction of the ethanol leaf extract of Landolphia owariensis. Methods: Qualitative phytochemical analyses were carried on the crude extract using standard methods. The alkaloid-rich fraction was obtained from the crude ethanol extract, using the classical acid/base shake-up method and the obtained fraction tested positive to Dragendorf’s reagent. Oral acute toxicity was evaluated by OECD method (No 423). Anti-inflammatory effect of the fraction was evaluated using xylene-induce ear oedema and carrageenan-induced paw inflammation in mice at doses of 100, 200 and 400 mg/kg. Results: Phytochemical screening revealed presence of alkaloids, flavonoids, tannins, saponins, steroids/terpenes and glycosides. Acute toxicity studies showed no adverse symptoms of toxicity during the 14-day observation period and no mortality was recorded, thus the LD50 was estimated to be greater than 2000 mg/kg. The alkaloid-rich fraction dose-dependently inhibited inflammation induced by xylene and carrageenan. In the xylene test, the fraction produced significant inhibition of 41.70 % at 400 mg/kg (p ≤ 0.05) while in the carrageenan test 55.69 % significant inhibition (p ≤ 0.001) was recorded with 400 mg/kg at 60 mins after induction of inflammation. Conclusion: This study showed the anti-inflammatory potentials of the alkaloid-rich fraction of Landophia owariensis.